The Desire for Parenthood: Gay Men Choosing to Become Parents Through Surrogacy. (August 2013) - Murphy, Dean A.
Gay men are becoming increasingly involved in reproduction despite significant barriers limiting their access to reproductive technologies or legal parentage in many jurisdictions. Based on in-depth interviews with gay men in the United States and Australia who have become parents through surrogacy, I explore how gay men understand their desire to have children and what frames their parenthood experiences. The notion of choice is widespread in understandings of gay parenthood and family formation. Most of the men in this study did not develop a "procreative consciousness" as a result of sexual and fertility-related events. The majority also initially accepted the notion that homosexuality was synonymous with childlessness. Awareness of the possibilities for parenthood emerged over time through the promotional activities of surrogacy agencies, through media, peers, and relationship partners. Additionally, men played with the symbols of kinship to negotiate and obscure biogenetic paternity.